The Impact of Avoidant/Disengagement Coping and Social Support on the Mental Health of Adolescent Victims of Sexual Violence in Eastern Congo - Verelst, An; Bal, Sarah; De Schryver, Maarten; Say Kana, Nanc; Broekaert, Eric; Derluyn, Ilse (Frontiers in Psychiatry, 2020)
Abstract The widespread use of sexual violence has made Congo, a region affected by war for several decades, home to many women and girls dealing with diverse sequelae of sexual violence. The impact of sexual violence on the psychosocial well-being of adolescent victims is devastating. Little is known however on the role of avoidant/disengagement coping and family support in determining the mental health impact of sexual violence. Methods A cross-sectional, population-based survey design was implemented in which 1,305 school-going adolescent girls aged 11 to 23 participated. Self-report measures of mental health symptoms (IES-R and HSCL-37A), family support (MSPSS), avoidant/disengagement (Kidcope), war-related traumatic events (ACEES), experiences of sexual violence, daily stressors and stigmatization (ACEDSS) were administered. Hierarchical multiple regression analysis was carried out with mental health outcomes as dependent variables for different types of sexual violence. Finally, several ANCOVA models were defined to explore possible interaction effects of avoidant/disengagement coping and family support with stigmatization, daily stressors and war-related traumatic exposure. Results Avoidant/disengagement coping has a direct negative effect on all psychological symptoms in girls who didn’t report sexual violence. For victims of sexual violence, the interaction effect between avoidance coping and stigmatization on different mental health scales (posttraumatic stress and anxiety) showed that when high levels of stigma are reported, avoidant/disengagement coping possibly served as a protective factor. Interestingly, high levels of daily stressors combined with avoidant/disengagement strategies were associated with a strong increase in posttraumatic stress symptoms. Family support did not mitigate the mental health outcomes of sexual violence. For girls who reported sexual violence but didn’t label it as rape and had a high level of family support, there was a positive association between stressors (daily stressors, stigma and war-related trauma) and posttraumatic stress symptoms. Conclusions These findings speak to the importance of looking beyond the unequivocal negative impact of avoidant/disengagement coping strategies on mental health in adolescent victims of sexual violence. Whilst avoiding/disengagement coping can have a negative impact on psychosocial well-being on adolescent victims of sexual violence, in case of high levels of stigmatization it can as well protect them from posttraumatic stress or anxiety.